Non-pharmacological interventions to improve the patient experience of colonoscopy under moderate or no sedation: a systematic review protocol - Nancy N Baxter; Jill Tinmouth; Diego Llovet; Teruko Kishibe; Colin Sue-Chue-Lam; Matthew Castelo (BMJ Open)
Introduction The patient experience is a critical dimension of colonoscopy quality. Sedative and analgesic drugs are commonly used to improve the patient experience of colonoscopy, with predominant regimens being deep sedation, typically achieved with propofol, and moderate sedation, typically achieved with an opioid and a benzodiazepine. However, non-pharmacological interventions exist that may be used to improve patient experience. Furthermore, by identifying non-pharmacological interventions to increase the quality of patient experience under moderate sedation, jurisdictions facing rising use of deep sedation for colonoscopy and its significant associated costs may be better able to encourage patients and clinicians to adopt moderate sedation. Advancing either of these aims requires synthesising the evidence and raising awareness around these non-pharmacological interventions to improve the patient experience of colonoscopy.Methods and analysis A systematic review will be conducted that searches multiple electronic databases from inception until 2020 to identify randomised controlled trials evaluating what, if any, non-pharmacological interventions are effective compared with placebo or usual care for improving the patient experience of routine colonoscopy under moderate or no sedation. Two reviewers will independently perform a three-stage screening process and extract all study data using piloted forms. Study quality will be assessed using the Cochrane Risk of Bias Tool V.2.0. Where multiple studies evaluate a single intervention, evidence will be quantitatively synthesised using pairwise meta-analysis, otherwise narrative syntheses will be undertaken.Ethics and dissemination This is a review of existing literature not requiring ethics approval. The review findings will be included in future efforts to develop an implementation strategy to reduce the use of deep sedation for routine colonoscopy. They will also be published in a peer-reviewed journal, presented at conferences and contribute to a doctoral thesis.PROSPERO registration number CRD42020173906.